Aplikasi Pengenalan Huruf Hijaiyah Untuk Penyandang Tunarungu Menggunakan Metode Sequential Search: Penerapan Metode Sequential Search dalam Aplikasi Pembelajaran Huruf Hijaiyah untuk Tunarungu - Fawaid, Muhammad Hasib; Ramadhani, Risky Aswi; Helilintar, Risa (Universitas Nusantara PGRI Kediri, 2024)
Hearing limitations are often an obstacle for deaf people in learning Arabic letters, including Hijaiyah letters. Deaf people are children with hearing impairments, either deaf or hard of hearing. The lack of learning media causes parents to experience learning problems in their children. Therefore, learning media is needed so that people with hearing disabilities can get easy learning, especially learning Hijaiyah letters. An introduction application is needed to facilitate learning, which is able to improve the ability to recognize hijaiyah letters easily. The main output of this research is photos and video demonstrations using the Sequential Search method. The Sequential Search method is used to facilitate the search for hijaiyah letters for students in the search for the application using Latin letters, implemented in Gerkatin Kediri city and using Kotlin programming language. The purpose of this research is to produce learning media that benefits deaf students in the introduction of Arabic including hijaiyah letters. The Sequential Search method is used to optimize the letter recognition process in this application. The supporting factor for the method used is logcat from the Android Studio application. Logcat helps the effectiveness of the sequential search method to run as desired. The test results of the search application show the time required to search for several hijaiyah letters with the keyword “Dal” is 0.235 ms, while for the letter Dzal it is 0.274 ms.